Radical Transformational Leadership Strategic Action for Change Agents - Sharma, Monica (California North Atlantic Books, 2017)
Monica Sharma describes how we can source our inner capacities and wisdom to manifest change that embodies universal values such as dignity, compassion, fairness, and courage. Drawing on more than twenty years of work for the United Nations and elsewhere, she presents a radical new approach to transformational leadership, one that creates systems of change where everyone can engage-not just analysts and policy-makers. Demonstrating that we all can be architects of a new humanity, Monica demystifies policy-making, planning, and implementation so that everyone can play an informed and strategic part in eradicating the world's most intractable problems. Using real-life examples from around the world, she shows how our innate characteristics of universal compassion, equity impulse, and human capability can create new patterns that effectively address major challenges such as gross inequality, unbridled hate, conflicts based on social identity, and the never-enough mind-set of greed. Written in a straightforward, accessible style, radical transformational leadership outlines a path-breaking paradigm shift that is already generating equitable and sustainable results across the globe. Winner of the nautilus gold Award for business and leadership.
Keywords: Leadership; Strategy